Retfærdiggørelse som troens indhold og teologiens norm - Põder, Christine Svinth-Værge; Kristensen, Johanne Stubbe Teglbjærg (Dansk Teologisk Tidsskrift, 2023)
Among the Confessions of the Danish Evangelical-Lutheran Church, the Augsburg Confession plays a special role as the one which, together with Luther’s Little Catechism, expresses the Lutheran identity of the Danish Evangelical-Lutheran Church. Among the Augsburg Confession’s articles, article number four has traditionally been considered the center of the entire confession and thus seen as an expression of the basic content of faith and hence also as the norm of theology. If one looks at the later, modern and contemporary Lutheran discussions of article four more closely, they concern above all discussions about how the connection between the content of faith and the norm of faith should be understood. In this contribution, we affirm the importance, depth and contemporary relevance of this discussion and propose an open interpretation that does not reduce Lutheran theology to a matter of either content or norm, but rather asks about the context of content and the limits and possibilities the methods of theology.